"Audacious limbs: dance as revolutionary praxis in Emily Holmes Coleman's surrealist novel, The Shutter of Snow". Issue 3 (2nd September 2022) - Coates, Kimberly
ABSTRACT: This article reads dance in Emily Holmes Coleman's, The Shutter of Snow (1930) as a revolutionary praxis. Situating the novel as influenced by the time Coleman spent living in Paris and publishing in transition at the height of Surrealism, I argue that dance, as practiced by Coleman's protagonist Marthe Gail, constitutes an embodied politics bent on resisting the threats posed to women's sexual and political autonomy by the nationalist and neo-natalist rhetoric associated with the rise of fascism.